Semantic web and its reflections in distance education - Sevindik, Tuncay; Kayisli, Korhan; Unlukahraman, Orhan (Elsevier Science Bv, 2010)
Due to the advances in web technology, sharing of information has become easier, but also more complicated. In searches through internet, search engines have been used and these search engines have also shown the content, un-related to the searches. The reason of this is that the data searched is only known to the searcher and can not be commented by the search engines. In solving all these problems, semantic web architecture, used as a new technology, was structured. The aim of this study is to determine what kind of usage area semantic web has in distance education platforms and to structure its ontological and architectural form. Moreover, URI and UNICODE, XML and RDF forms will be determined with their usage styles in distance education platforms. In conclusion, the semantic web-based properties of education environments are determined. (C) 2010 Elsevier Ltd. All rights reserved.
2nd World Conference on Educational Sciences (WCES-2010) -- FEB 04-08, 2010 -- Bahceschir Univ, Istanbul, TURKEY
Keywords: Education; ontology; semantic; technology; web